Klesas and Pretas: Therapy and Liberation in Buddhist Recovery from Addiction - Dossett, Wendy (Implicit religion, 2019)
This article offers an analysis of Buddhist approaches to addiction recovery in the terms of some of the key debates in addiction/recovery studies. Buddhist recovery teachings are analysed for the extent to which they embody models of addiction which construe the problem as a disease, as a moral problem, as a problem of powerlessness, as a problem of control, as a choice, as a social or a personal problem, and as continuous (or not) with putative sa?sāric experience. They are also analysed for the extent to which recovery is modelled as a change of identity or of practices, and how far recovery ideals' align with Buddhist soteriology. The article exposes philosophical and epistemological diversity across Buddhist recovery pathways, and argues that the therapeutization of Buddhism (Metcalf 2002) is inadequate as a categorical frame